AN ANALYSIS OF TYPES AND CAUSES OF TRANSLATION ERRORS - Tia Aprilianti Putri (Department of Master of Linguistic, Universitas Airlangga, 2019)
Translation is a process of changing an original text from one language into another. Nowadays its role is important in almost every single aspect of human’s life. Since its role becomes more vital, the quality of the result of translation must be qualified as well. Doing translation is not an easy task, it is a combination of skill and art. The translators should have enough knowledge about the important aspects from both source language and target language. However there are still many difficulties appear while doing translation. Those difficulties lead the translators make errors while translating. After reviewing some research conducted, the writer of this research discovers the types of translation errors and the causes which lead the errors done by many translators. The most dominant types of errors in translation experienced by the translators lie in surface structure such as semantic, lexical, morphology, and grammar errors. However another type of errors in translation lies in deep structure which is connected with culture differences between both source and target language. The second discovery is about the causes of errors in translation. The most common causes is lack of knowledge about linguistic aspect of the target language can cause the errors. Another primary factor is the anxiety of the translators themselves causes the errors in translation.